Plasma IL-6/IL-10 Ratio and IL-8, LDH, and HBDH Level Predict the Severity and the Risk of Death in AIDS Patients with Pneumocystis Pneumonia - Jia Sun; Junwei Su; Yirui Xie; Michael T. Yin; Ying Huang; Lijun Xu; Qihui Zhou; Biao Zhu (Journal of Immunology Research)
Objective. To identify blood biomarkers to predict severity and mortality in AIDS PCP patients. Methods. Biomarkers including clinical parameters and plasma inflammatory cytokines were assessed in 32 HIV-infected patients with Pneumocystis pneumonia (PCP) at time of admission. Predictive value of the biomarkers for clinical severity and in-hospital mortality was evaluated by corresponding ROC curve. Results. Levels of CRP, WBC, LDH, HBDH, and Ferritin were significantly higher in the severe and nonsurvivor AIDS PCP patients. These important biochemical indicators have inverse correlation with oxygenation index, especially levels of LDH (P=0.008, R2=0.258), HBDH (P=0.001, R2=0.335), and Ferritin (P=0.005, R2=0.237). Plasma IL-8 and IL-6 levels were significantly higher in patients with PaO2/FiO2 ≤ 200 mmHg and nonsurvivors than in those with PaO2/FiO2 > 200 mmHg and survivors. Severe and nonsurvival groups showed higher ratio of mean IL-6/IL-10 level (1.78 ± 1.56, P<0.001; 1.11 ± 0.72, P=0.043), larger AUC (95% CI 0.781–1.000, P<0.001; 95% CI 0.592–0.917, P=0.043), and more significantly inverse correlation with the oxygenation index. Conclusion. Plasma IL-8, LDH, and HBDH levels and IL-6/IL-10 ratio could be helpful for early evaluation of the severity and predicting fatal outcomes in AIDS PCP patients.